Producción de sorgos para reserva de forraje (henificación/ensilaje) en el Valle Inferior del Río Negro Campaña 2008-2009 - Miñon, Daniel Pedro; Gallego, Juan Jose; Murray, Francisco; Barbarossa, Raul Antonio (EEA Valle Inferior, INTA, 2021)
EEA Valle Inferior